Observation of quantum entanglement with top quarks at the ATLAS detector - Aad, G.; Åkesson, T.P.A. ; 0000-0003-4141-5408; Doglioni, C.; Ekman, P.A. ; 0000-0002-7032-2799; Hedberg, V.; Herde, H. ; 0000-0001-8926-6734; Konya, B.; Lytken, E. ; 0000-0002-8141-3995; Poettgen, R. ; 0000-0002-3304-0987; Simpson, N.D.; Smirnova, O. ; 0000-0003-2517-531X; Zwalinski, L. (Nature, 2024)
Entanglement is a key feature of quantum mechanics1–3, with applications in fields such as metrology, cryptography, quantum information and quantum computation4–8. It has been observed in a wide variety of systems and length scales, ranging from the microscopic9–13 to the macroscopic14–16. However, entanglement remains largely unexplored at the highest accessible energy scales. Here we report the highest-energy observation of entanglement, in top–antitop quark events produced at the Large Hadron Collider, using a proton–proton collision dataset with a centre-of-mass energy of √s = 13 TeV and an integrated luminosity of 140 inverse femtobarns (fb)−1 recorded with the ATLAS experiment. Spin entanglement is detected from the measurement of a single observable D, inferred from the angle between the charged leptons in their parent top- and antitop-quark rest frames. The observable is measured in a narrow interval around the top–antitop quark production threshold, at which the entanglement detection is expected to be significant. It is reported in a fiducial phase space defined with stable particles to minimize the uncertainties that stem from the limitations of the Monte Carlo event generators and the parton shower model in modelling top-quark pair production. The entanglement marker is measured to be D = −0.537 ± 0.002 (stat.) ± 0.019 (syst.) for 340GeV
Keywords: Elementary Particles; Protons; Quantum Theory; proton; collision; data set; energy management; experimental study; Monte Carlo analysis; quantum mechanics; scale effect; Article; astronomy; cryptography; hadron; large hadron collider; luminance; metrology; polarization; quantum computation; quantum entanglement; quantum information; elementary particle; quantum theory